1985
DOI: 10.1128/mcb.5.9.2181
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of influenza virus neuraminidase, an amino-terminally anchored viral membrane glycoprotein, in polarized epithelial cells.

Abstract: We have investigated the site of surface expression of the neuraminidase (NA) glycoprotein of influenza A virus, which, in contrast to the hemagglutinin, is bound to membranes by hydrophobic residues near the NH2-terminus. Madin-Darby canine kidney or primary African green monkey kidney cells infected with influenza A/WSN/33 virus and subsequently labeled with monoclonal antibody to the NA and then with a colloidal gold-or ferritin-conjugated second antibody exhibited specific labeling of apical surfaces. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Sphingolipid-and cholesterol-containing rafts have been proposed to be important for apical transport in polarized epithelial cells (55). Wild-type HA, NA, and M 2 are expressed at the apical surface of polarized cells (19,24,49). Previous studies indicated that alteration of residues in the TM domains of HA and NA can affect both DIG association and apical targeting, although the correlation was not absolute (28, 34, 53).…”
Section: Resultsmentioning
confidence: 97%
“…Sphingolipid-and cholesterol-containing rafts have been proposed to be important for apical transport in polarized epithelial cells (55). Wild-type HA, NA, and M 2 are expressed at the apical surface of polarized cells (19,24,49). Previous studies indicated that alteration of residues in the TM domains of HA and NA can affect both DIG association and apical targeting, although the correlation was not absolute (28, 34, 53).…”
Section: Resultsmentioning
confidence: 97%
“…Since further deletion in the 3Ј end leaving only 15 nucleotides and of the 5Ј end leaving 268 nucleotides did not affect the efficiency of HA vRNA incorporation [compare HA(468)GFP(513) with HA(15)GFP(268)], we made additional deletion constructs by using pPolIHA (15)GFP(268), which possessed 15 nucleotides of the 3Ј end of the HA coding region and 268 nucleotides of the 5Ј end. Although the extent of vRNA incorporation was reduced gradually as the extent of deletions increased, 80 nucleotides in the 5Ј HA coding region seemed minimally required for efficient virion incorporation of the HA vRNA [compare HA (15) GFP(80) with HA(15)GFP (75)]. Further deletion analysis demonstrated that HA(9)GFP(80) with 9 nucleotides at the 3Ј end of the HA coding region resulted in efficient virion incorporation of the HA vRNA (Ͼ65%); however, the level of HA(9)GFP(80) vRNA present in transfected cells did not differ appreciably from that of HA(0)GFP(0) vRNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the information for protein sorting is contained within the glycoprotein structure (Roth et aI., 1983;Jones et at., 1985;Stephens et al, 1986;Puddington et al, 1987), polarized budding can be viewed simply as the result of transport of M protein and nucleocapsids orchestrated by the glycoprotein.…”
Section: Discussionmentioning
confidence: 99%